2019
DOI: 10.1039/c8ta11487k
|View full text |Cite
|
Sign up to set email alerts
|

In situ generated 3D hierarchical Co3O4@MnO2 core–shell hybrid materials: self-assembled fabrication, morphological control and energy applications

Abstract: A new series of highly ordered 3D hierarchical Co3O4@MnO2 core–shell hybrid materials was developed by a simple in situ self-assembly strategy for two typical energy applications in DSSCs and AP decomposition with superior performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Mixing these two classes of materials provides a nanocomposite material with collaboration and coping effects that create oxygen vacancies, which improves the ORR activity [19,20]. To enhance the electrochemical performance of the catalysts for ORR, nanocomposite catalysts such as CuO@MnO 2 [21], NiCo 2 O 4 @MnO 2 [22], TiO 2 @MnO 2 [23], ZnO/MnO 2 [24], Fe 2 O 3 -MnO 2 [25], Co 3 O 4 /MnO 2 -CNTs [26], and Co 3 O 4 @MnO 2 [27] have been investigated. The synergetic effect of the individual components allows the nanocomposite structure to exhibit improved characteristics [28].…”
Section: Introductionmentioning
confidence: 99%
“…Mixing these two classes of materials provides a nanocomposite material with collaboration and coping effects that create oxygen vacancies, which improves the ORR activity [19,20]. To enhance the electrochemical performance of the catalysts for ORR, nanocomposite catalysts such as CuO@MnO 2 [21], NiCo 2 O 4 @MnO 2 [22], TiO 2 @MnO 2 [23], ZnO/MnO 2 [24], Fe 2 O 3 -MnO 2 [25], Co 3 O 4 /MnO 2 -CNTs [26], and Co 3 O 4 @MnO 2 [27] have been investigated. The synergetic effect of the individual components allows the nanocomposite structure to exhibit improved characteristics [28].…”
Section: Introductionmentioning
confidence: 99%
“…16 This structure is often associated with large surface area and more bust shell, leading to improved stability. 17 Miao et al 18 developed a route for 3D hierarchical Co 3 O 4 @MnO 2 core−shell materials for energy application of photoelectric conversion devices of dyesensitized solar cells. Luo et al 19 reported a one-pot two-step route to prepare Mn 3 O 4 @CoMn 2 O 4 as efficient nanoparticles metal bifunctional oxygen catalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The O 1s of Co 3 O 4 -120, Co 3 O 4 -160, and Co 3 O 4 -200 could be deconvoluted to two main peaks. The binding energy of 530.18 eV was assigned to the lattice O 2– oxygen ions, while the binding energy of 531.64 eV could be usually assigned to surface active oxygen. , Generally, the performance of the toluene catalytic combustion is tightly related to the surface active oxygen species of catalysts. The accurate content of surface active oxygen species and the molar ratios are calculated by a quantitative analysis method on the O 1s XPS spectra, and the results are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%